Ethylene is involved in strawberry fruit ripening in an organ-specific manner. - Merchante, Catharina; Valpuesta, Victoriano; Vallarino, José G.; Osorio-Algar, Sonia; Aragüez, Irene; Villareal, Natalia; Ariza, Maria T.; Martínez, Gustavo A.; Medina-Escobar, Nieves; Civello, Marcos P.; Fernie, Alisdair R.; Botella-Mesa, Miguel Ángel (Oxford Academic, 2013)
The fruit of the strawberry F.ananassa has traditionally been classified as non-climacteric because its ripen- ing process is not governed by ethylene. However, previous studies have reported the timely endogenous production of minor amounts of ethylene by the fruit as well as the differential expression of genes of the ethylene synthesis, reception, and signalling pathways during fruit development. Mining of the F.vesca genome allowed for the identification of the two main ethylene biosynthetic genes, 1-aminocyclopropane-1-carboxylic acid (ACC) synthase and ACC oxidase. Their expression pattern during fruit ripening was found to be stage and organ (achene or recepta- cle) specific. Strawberry plants with altered sensitivity to ethylene could be employed to unravel the role of ethylene in the ripening process of the strawberry fruit. To this end, independent lines of transgenic strawberry plants were generated that overexpress the Arabidopsis etr1-1 mutant ethylene receptor, which is a dominant negative allele, causing diminished sensitivity to ethylene. Genes involved in ethylene perception as well as in its related downstream processes, such as flavonoid biosynthesis, pectin metabolism, and volatile biosynthesis, were differently expressed in two transgenic tissues, the achene and the receptacle. The different transcriptional responsiveness of the achene and the receptacle to ethylene was also revealed by the metabolic profiling of the primary metabolites in these two organs. The free amino acid content was higher in the transgenic lines compared with the control in the mature achene, while glucose and fructose, and citric and malic acids were at lower levels. In the receptacle, the most con- spicuous change in the transgenic lines was the depletion of the tricarboxylic acid cycle intermediates at the white stage of development, most probably as a consequence of diminished respiration.
Keywords: Fresas - Maduración; Etileno; Perfil metabólico; Strawberry; Fruit; Ethylene; Ripening